2020
DOI: 10.1007/s00289-020-03169-5
|View full text |Cite
|
Sign up to set email alerts
|

Sorbent system based on organosilane-coated polyurethane foam for oil spill clean up

Abstract: In this study, flexible and open cell polyurethane foams were formulated and chemically modified with organosilane to be used as a sorbent system for oil spill cleanup. Six polyurethane foams with different densities and three oil types with different viscosities were investigated. Moreover, sorbents were characterized based on their surface modification and sorption capacities. The main results indicated that the surface treatment on the solid fraction of the foam was effective, observing by the contact angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…CA greater than 90° in PU foams can enhance interaction with oily (nonpolar) substances. Consequently, this fact can benefit the process of vegetable oil adsorption in an aqueous medium for the foams developed in this article 65 . Figure 3(a) shows that PU‐composites and pristine PU have CA > 90°, which can classify the foams as hydrophobic.…”
Section: Resultsmentioning
confidence: 90%
“…CA greater than 90° in PU foams can enhance interaction with oily (nonpolar) substances. Consequently, this fact can benefit the process of vegetable oil adsorption in an aqueous medium for the foams developed in this article 65 . Figure 3(a) shows that PU‐composites and pristine PU have CA > 90°, which can classify the foams as hydrophobic.…”
Section: Resultsmentioning
confidence: 90%
“…[30][31][32] PU could be also modied or functionalized for improvement the oil uptake ability. 30,33,34 Taking all these factors into consideration, it is urgent to nd out a new environmentally friendly material with a high oil adsorption capacity by combination of hydrophobic synthetic PU and lignocellulosic waste.…”
Section: Introductionmentioning
confidence: 99%
“…To selectively absorb only oil from an oil–water mixture, the focus has mostly been on fabricating materials that are superhydrophobic (with a water contact angle of >150° on the absorbent) and superoleophilic (with an oil contact angle of <15° on the absorbent) or superhydrophobic and oleophilic (with an oil contact angle of <90° on the absorbent). Many researchers have utilized hydrophobic polymers, such as polystyrene and polydimethylsiloxane, for the needed wettability. Other studies have incorporated fluoro materials to increase hydrophobicity. , In a recent review, Sam and co-workers summarized several methods for surface engineering sponges, including cellulose sponges, to improve their surface hydrophobicity, in particular, to change the sponges’ surface wettability to superhydrophobic and superoleophilic by using hydrophobic agents, such as organosilanes, , either alone , or in combination with other nanomaterials. , While superhydrophobic sponges are common in most studies, Minju et al have reported the use of hydrophobic alkylsilane modified sponges that had water contact angles between 100° and 125° and oil contact angles of ∼0° to selectively and completely absorb various oils from seawater. Hydrophobic foams of polyurethane modified with organosilane, having water contact angles of 105–110°, also resulted in a high oil collection capability in the study by Zimmermann et al These latter studies clearly illustrated that hydrophobic, not necessary superhydrophobic, sponges were sufficient for selective removal of oil from water. However, it was unclear whether a superoleophilic sponge is required for effective oil uptake.…”
Section: Introductionmentioning
confidence: 99%
“…15,20 In a recent review, Sam and co-workers summarized several methods for surface engineering sponges, including cellulose sponges, 21 to improve their surface hydrophobicity, in particular, to change the sponges' surface wettability to superhydrophobic and superoleophilic by using hydrophobic agents, such as organosilanes, 2,11 either alone 22,23 or in combination with other nanomaterials. 24,25 While superhydrophobic sponges are common in most studies, Minju et al 26 have reported the use of hydrophobic alkylsilane modified sponges that had water contact angles between 100°a nd 125°and oil contact angles of ∼0°to selectively and completely absorb various oils from seawater. Hydrophobic foams of polyurethane modified with organosilane, having water contact angles of 105−110°, also resulted in a high oil collection capability in the study by Zimmermann et al 24 These latter studies clearly illustrated that hydrophobic, not necessary superhydrophobic, sponges were sufficient for selective removal of oil from water.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation